Furazan‐Fused Azacyclic Nitramines: Influence of Structural Features on the Combustion and the Thermolysis. Issue 44 (23rd November 2020) - Sinditskii, Valery P.; Smirnova, Anastasia D.; Serushkin, Valery V.; Aleksandrova, Natali S.; Sheremetev, Aleksei B.
Abstract: The combustion behavior and thermal stability of 4, 6, 8‐trinitro‐4, 5, 7, 8‐tetrahydro‐6H‐furazano[3, 4‐f]‐1, 3, 5‐triazepine (FRDX) and 1, 4, 5, 8‐tetranitrodifurazano[3, 4‐c][3, 4‐h]tetraazadecaline (FTNAD) were investigated and compared with analogs, where the furazan ring is substituted with CH2 or C=O units. It has been shown that the furazan‐fused unit reduces the thermal stability of azacyclic nitramines, probably due to the weakening of the N−NO2 bond. The burning rates of FRDX and FTNAD are determined by the kinetics of heat release in the melt. There is the peculiar effect of the furazan unit on the burning rate: according to thermocouple measurements, the unit increases the volatility of cyclic nitramines and reduces the temperature of the burning surface, which should lead to a decrease in the burning rate, but on the other hand, it simultaneously increases the rate of heat release in the melt, and as a result, the burning rate increases rather than falls. Abstract : A building block for the design of energetic compounds, such as a furazan ring, in combination with azacyclic nitramine cores, increases the burning rate and the vapor pressure, but reduces the thermal stability of the target molecules.